The impact of secondary school students’ perceptions of parental academic involvement and academic stress on internalizing problem behaviors: the mediating roles of psychological resilience and materialism - Xue, Li (Frontiers in Psychology, 2025)
IntroductionThis study aimed to examine how perceived parental academic involvement and stress influence internalizing problem behaviors (i.e., depression and anxiety symptoms) among secondary school students in international schools, focusing on the mediating roles of psychological resilience and materialistic values.MethodA cross-sectional survey was conducted among 412 secondary school students (Mage = 16.28 years; 50.2% female) from international schools in Mainland China. Participants completed validated questionnaires assessing perceived parental academic involvement and stress, psychological resilience (CD-RISC-10), materialism (MVS), depression (PHQ-9), and anxiety (GAD-7). Hayes’ PROCESS macro 4.0 (Model 4) with bootstrapping (5,000 samples, 95% CI) was used to examine the parallel mediation effects. This population was selected due to the unique cultural and academic stressors faced by international school students, such as cross-cultural adjustment and elevated academic demands.Results and discussionPerceived parental academic involvement negatively predicted internalizing problem behaviors, while perceived parental academic stress was positively associated with them. Psychological resilience and materialism both significantly mediated the relationship between parental academic stress and internalizing symptoms. However, only psychological resilience—not materialism—mediated the effect of parental academic involvement. Moreover, perceived parental involvement did not significantly predict adolescent materialism. The findings suggest that fostering psychological resilience and addressing materialistic values may help buffer the negative impact of academic stress on adolescents’ mental health. While the results provide valuable insights into the emotional adjustment of international school students, caution is advised in generalizing the findings to other student populations.